Modal analysis of computational guitar model using finite elements and impulse excitation method (Research, Society and Development, 2021)
A guitar is constructed essentially of wood. However, each wood brings with it some specific characteristics. Its acoustic behavior is related to the elastic properties of the materials that compose it. It is known that the elastic properties of materials interfere not only in their mechanical resistance, but also in their dynamic behavior; a structure can vibrate more or less intensely depending on the material that composes it and its elastic properties. The present work analyzes the dynamic behavior of a computational guitar model through modal analysis calculated by the finite element method (MEF) applying boundary conditions that simulate the stiffness of the lateral bands and the tension of the strings on the easel and neck, obtaining answers in terms of natural frequencies and the corresponding forms of vibration modes. And so, compare with frequency responses obtained experimentally through the method of pulse excitation. The results show that the responses in numerical natural frequencies are similar to the values ​​obtained experimentally, indicative of belonging to the same mode of vibration.